Clinical profile and impact of comorbidities in patients with very‐late‐onset myasthenia gravis. Issue 4 (21st July 2021) - Vijayan, Joy; Menon, Deepak; Barnett, Carolina; Katzberg, Hans; Lovblom, Leif Erik; Bril, Vera
Abstract: Introduction/Aims: The purpose of this study was to evaluate the clinical profile of myasthenia gravis (MG) in older patients and determine the impact of medical comorbidities on their MG status and outcome. Methods: This was a retrospective chart review of patients with a symptom onset of MG at or after 65 years of age. Correlations were made between demographics, clinical characteristics, the Myasthenia Gravis Foundation of America (MGFA) severity scale scores, and Myasthenia Gravis Impairment Index (MGII) scores with two outcome measures: MGFA Post‐Intervention Status (MGFA‐PIS) and Simple Single Question (SSQ). Results: The study population included 109 patients, with 90 of them having more than one follow‐up visit. Their mean age was 75.3 ± 6.9 years and sex distribution was even. Of these patients, 67.7% had generalized MG. Nine‐one percent of patients had one comorbidity. None of the demographic factors or comorbidities showed an association with MGFA‐PIS, SSQ, or MGII after correction for multiple comparisons. Seventy‐one percent of the patients improved with treatment, 12.4% remained unchanged, and 16.6% showed worsening at their last follow‐up visit. Discussion: Our study shows that patients with very‐late‐onset MG had a good prognosis and treatment response. None of the comorbidities had an impact on the severity of myasthenic symptoms or on outcome in these patients.